Problem-Based Learning: Learning Approach Solutions in Crisis Period - Mahendra, I Wayan Eka; Sugiharni, Gusti Ayu Dessy (Journal of Education Reseach and Evaluation, 2022)
Currently, there are many schools that apply poor learning activities using conventional approaches during the Covid-19 pandemic. Moreover, it is suspected that there has been a learning loss. Therefore, a learning approach is needed that can improve student learning activities which lead to an increase in students' higher order thinking skills (HOTS). Therefore, the aim of this study is to analyze the application of online PBL in its effect on student`s thinking abilities. This research was conducted at State Junior High Schools which involving a sample of 78 students who were taken using a simple random sampling technique. The students' higher-order thinking skills (HOTS) were collected by using the test which has examined its validity and reliability coefficients. The collected data were analyzed using the t-test which has initially examined the normality of the data distribution and the homogeneity of the variants. The results of this study indicated that there was an effect of implementing a problem-based learning (PBL) approach on the students' higher-order thinking skills (HOTS).